The Effect Of Using Sign Language - Based Basic Life Support Video Media On The Level Of Knowladge Of BLS In The Deaf In Darul 'Ashom Islamic Boarding School: Pengaruh Penggunaan Media Video Bantuan Hidup Dasar Berbasis Bahasa Isyarat Terhadap Tingkat Pengetahuan BHD Pada Tunarungu Di Pondok Pesantren Darul ‘Ashom - Ni'matul Fauziyyah, Hamla; Badiah, Atik; Laasara, Nurun (Poltekkes Kemenkes Yogyakarta, 2023)
Assistance for cardiac arrest and respiratory arrest must be carried out immediately without waiting for medical personnel, the way is by giving Basic Life Support (BLS). Education about BLS is a way to increase knowledge. Deaf people need access as needed to support increased knowledge about BLS. Purpose of reserch is to determine the effect of the use of sign language-based basic life support video media on the level of BLS knowledge of the deaf at the Darul 'Ashom Islamic Boarding School. This research is a quasi experiment using a one group pre test – post test design. This research was conducted in March - April 2023. The population for this research study were students of the Darul 'Ashom Islamic Boarding School aged 15-22 years with a total of 20 students. Data analysis using paired t-test. The average score of BLS knowledge before giving sign-based video media was 54, while the average score of BLS knowledge after giving sign-based video media was 76. The results showed that there was an effect of using sign language-based basic life support video media on the level of BHD knowledge in deaf at the Darul 'Ashom Islamic Boarding School. (p=0.000). There is an effect of the use of sign language-based basic life support video media on the level of BLS knowledge of the deaf at the Darul 'Ashom Islamic Boarding School. Pertolongan henti jantung dan henti napas harus segera dilakukan tanpa menunggu tenaga medis yaitu dengan memberikan Bantuan Hidup Dasar (BHD). Pendidikan tentang BHD merupakan cara untuk meningkatkan pengetahuan. Tunarungu membutuhkan akses ramah tunarungu untuk mendukung peningkatan pengetahuan tentang BHD. Penelitian ini untuk mengetahui pengaruh penggunaan media video bantuan hidup dasar berbasis bahasa isyarat terhadap tingkat pengetahuan BHD pada tunarungu di Pondok Pesantren Darul ‘Ashom. Metode penelitian ini adalah quasi eksperimen dengan menggunakan rancangan one group pre test – post test. Penelitian ini dilaksanakan pada bulan Maret – April 2023. Populasi studi penelitian ini adalah santri Pondok Pesantren Darul ‘Ashom usia 15-22 tahun dengan jumlah 20 santri. Analisis data menggunakan paired t-test. Hasil yang didapatkan adalah rata-rata skor pengetahuan BHD sebelum pemberian media video berbasis isyarat adalah 54, sedangkan rata-rata skor pengetahuan BHD setelah pemberian media video berbasis isyarat adalah 76. Hasil penelitian menunjukan adanya pengaruh penggunaan media video bantuan hidup dasar berbasis bahasa isyarat terhadap tingkat pengetahuan BHD pada tunarungu di Pondok Pesantren Darul ‘Ashom. (p=0.000). Terdapat pengaruh penggunaan media video bantuan hidup dasar berbasis bahasa isyarat terhadap tingkat pengetahuan BHD pada tunarungu di Pondok Pesantren Darul ‘Ashom.